Controlling calving intervals with prostaglandin F2αand fixed-time inseminations - Stevenson, Jeffrey S.; Lucy, M.C.; Call, Edward P. (Kansas Agricultural Experiment Station, 2012)
Prolonged or delayed interval to first breeding is a major cause of long calving intervals. Our objective was to test two methods of artificial insemination by appointment after controlling the onset of estrus for all first breedings after calving. Prostaglandin F2α (PGF) was used to time the onset of estrus for cows in two experimental groups. Control cows (inseminated at first heat after 42 days postpartum) had longer intervals to first breeding than the two experimental groups given PCF at 40 to 46 and 51 to 57 days postpartum. Conception rates were lower in the treated cows than in control cows. However, no differences were observed for calving intervals, which ranged in average days from 379 to 384 for treated cows and averaged 376 days for control cows. We were able to reduce successfully the interval to first breeding so all cows were first bred by approximately 60 days postpartum in the experimental groups, but we were unable to shorten overall calving intervals.
Keywords: Dairy; Prostaglandin F2-alpha; Fixed-time AI; Estrus; Conception rates